P‐116: The Investigation of In‐Plane Liquid Crystal Photo‐Alignment Technology for Large Size Panel. Issue 1 (June 2015) - Song, Yan‐Jun; Hsieh, Chung‐Ching; Zhao, Yong‐Chao; Zhao, Ren‐Tang; Li, Xiang; Chiu, Chung‐Yi; Lee, Chia‐Yu; Lo, Chang‐Cheng; Lien, Alan
Abstract : A new photo alignment material for fringe field switching (FFS) and in‐plane switching (IPS) liquid crystal display has been presented and it has good alignment performance. It realizes alignment by irradiating linearly polarized light with wavelength of 365nm. We have investigated the effect of UV dosage and anneal process on the alignment ability and optical performance. An excellent dark state and image sticking property can be achieved by optimized photo alignment conditions.